(untitled) (Palíndromo, 2021)
This visual essay presents the arrangement of eight radiographies digitally edited by the visual artist, performer, art teacher Pedro Gottardi, linked to the Master’s in Education at the Regional University of Blumenau (FURB). Anthropophagic dilatation is part of his studies, whose origin came from an accident during the execution of the performance art “Celebration of Our Flesh”, in 2018 - an initiative of the artist and Master’s student, at the Research Group Art and Aesthetics in Education (Grupo de Pesquisa Arte e Estética na Educação - GPAEE). Performance art was idealized in the curricular component History of Art V, during the final phase of his teaching degree in the Visual Arts Course at FURB. The text is written in a biographical form, bringing to light his account of what he experienced. It constitutes a poetic hybridism that articulates the aesthesias experienced in the aesthetic education of teachers in Visual Arts